Trends in Presentation, Management, and Survival of Women With Breast Cancer in a Multiethnic, Middle-Income Asian Setting - Sharminii Jaya-Prakason; Yek-Ching Kong; Cheng-Har Yip; Mee-Hoong See; Nur Aishah Taib; Nur Fadhlina Abdul Satar; Suniza Jamaris; Li Ying Teoh; Rose Irnawaty Ibrahim; Nirmala Bhoo-Pathy (American Society of Clinical Oncology, 2024)
Indexed by WOS/ Scopus